"Click" functionalization of dual stimuli-responsive polymer nanocapsules for drug delivery systems. Issue 20 (31st March 2017) - Yang, Wen Jing; Zhao, Tingting; Zhou, Peng; Chen, Simou; Gao, Yu; Liang, Lijun; Wang, Xiaodong; Wang, Lianhui
Abstract : "Clickable" and dual stimuli-responsive nanocapsules were developed for facile surface functionalization via thiol–yne click chemistry and employed as drug nano-carriers. Abstract : Surface decoration of nano-carriers is of great importance in targeted drug delivery systems. However, the surface coupling of functional ligands to nano-carriers usually involves sophisticated conjugation chemistry, such as carbodiimide-mediated amide coupling. Herein, "clickable" nanocapsules, containing reactive alkyne groups, were developed for surface functionalization via highly efficient thiol–yne click chemistry and further applied as intelligent drug nano-carriers. Firstly, by employing the facile reflux-precipitation polymerization, the "clickable" nanocapsules with dual thermal and redox responsive properties were readily prepared for further surface functionalization. The "clickable" nanocapsules were subsequently decorated with various functional ligands, including cysteine-folic acid, cysteine-RGD peptide and thiol-functionalized fluorescein isothiocyanate (SH-FITC). Finally, the folate acid-modified nanocapsules (FA-Nanocapsules) were explored as effective drug nano-carriers for doxorubicin (DOX) with triggered release behaviours due to the disulfide linkages and thermo-responsive poly(NIPAAm) components in the nanocapsules. The good growth inhibition of HeLa cells by DOX loaded FA-Nanocapsules indicated that the nanocapsules can be employed as promising drug delivery nano-carriers. The as-prepared dual stimuli-responsive nanocapsules, containing reactive alkyne groups, thus provide a versatile "clickable" platform for surface decoration and functionalization via highly efficient click chemistry.